2017
DOI: 10.1016/j.apenergy.2017.06.022
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the impact of tidal stream energy extraction on the Lagrangian circulation

Abstract: Whereas numerous numerical modelling have been conducted to gain further insights about the hydrodynamic characteristics of tidal stream energy sites, the long-term transport of water particles has been routinely ignored. However, a refined evaluation of circulation pathways is fundamental to assess water-quality changes induced by tidal energy converters. The present study investigates the tide-induced Lagrangian circulation in north-western coastal waters of Brittany (France, western Europe), including numer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
31
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(38 citation statements)
references
References 45 publications
7
31
0
Order By: Relevance
“…This asymmetry is associated with a prominent flood-dominated region in the north of the strait with residual currents up to 0.8 m s −1 and an ebb-dominated area in the south. Such current asymmetry is typical of tidal strait dynamics as confirmed by numerical investigations conducted in the potential stream energy sites of Orkney [8] or the Fromveur Strait [13,20]. Moreover, the divergence area, with reduced current asymmetry in the center of the strait, presents, most of the time, the strongest tidal currents.…”
Section: Tidal Current Asymmetrymentioning
confidence: 70%
See 2 more Smart Citations
“…This asymmetry is associated with a prominent flood-dominated region in the north of the strait with residual currents up to 0.8 m s −1 and an ebb-dominated area in the south. Such current asymmetry is typical of tidal strait dynamics as confirmed by numerical investigations conducted in the potential stream energy sites of Orkney [8] or the Fromveur Strait [13,20]. Moreover, the divergence area, with reduced current asymmetry in the center of the strait, presents, most of the time, the strongest tidal currents.…”
Section: Tidal Current Asymmetrymentioning
confidence: 70%
“…However, except local studies such as simulations conducted by Neill et al [8] in Orkney archipelago, Lewis et al [7] in the Irish sea or Guillou and Chapalain [13] in the Fromveur Strait (western Brittany, France), few numerical modeling studies have investigated the asymmetry and misalignment of tidal currents and its effects on the generated technical resource, at the scale of potential stream energy sites.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, previous studies were essentially performed with regional models where the turbines' thrust was spatially averaged over the area occupied by the tidal farm. This (spatially averaged) turbine representation implies that the interactions between the turbines' wakes are negated [5][6][7][8][9][10][11]. Such regional approach has been used at sites located in West Brittany such as the Sein Race [7] and the Fromveur strait [8], at Scottish sites such as the Orkney archipelago [9], at the Ramsey Sound strait [10], and at the Normand site of the Raz Blanchard [1].Recent works [11][12][13][14] deal with the implementation of methods developed (based on numerical results or experimental mapping) to optimize the identification of suitable sites for energy extraction.…”
mentioning
confidence: 99%
“…Thus, in this work, we perform resource characterization of Nigeria's tidal energy resources, for selected sites, together with an LCOE analysis of the respective sites. Several studies have been reported on geographical sites in various parts of the world, to the assessment of the potential for tidal current energy utilization [4][5][6][7][8][9]. Tidal current technology continues to progress rapidly particularly in the United Kingdom.…”
Section: Introductionmentioning
confidence: 99%